USE OF CHITOSONIUM MALATE AS A MATRIX IN SUSTAINED-RELEASE TABLETS - (:unkn) unknown (ELSEVIER SCIENCE BV, 1993)
A salt of chitosan (chitosonium malate) was examined as a matrix for sustained-release tablets. Furosemide was chosen as a model drug in this study. Sustained-release tablets were prepared by direct compression and wet-granulation techniques. Sustained-release properties of chitosan and chitosonium malate were compared. The effect of different concentrations of chitosonium malate (5, 10, 30 and 50%; formulations I-IV) on drug release profiles was studied. As the concentration of chitosonium malate increased, the rate of release of the drug decreased. Chitosonium malate shows sustained-release properties even at low concentrations. The results are examined kinetically and the mechanism is discussed. When the release data were fitted to the simple power law equation, the mode of drug release was of the non-Fickian and super case II types.
Keywords: CHITOSAN; CHITOSONIUM MALATE; SWELLING CONTROL; TABLETS; FUROSEMIDE; DIRECTLY COMPRESSIBLE TABLETS; RELEASE MECHANISM; SOLUTE RELEASE; CHITOSAN; FORMULATION; MECHANISMS; POLYMERS; SYSTEMS; NUMBER